An ethnohistorical dictionary of China - Olson, James Stuart, 1946- (Gale virtual reference library, 1998)
Designed to give readers a ready reference for background information on interpreting ethnic events in China. Provides essays on hundreds of Chinese ethnic groups, including ethnic groups living in the Republic of China on Taiwan.